What are the barriers to sustaining a safe sleep program for infants within hospital settings: An integrative review of the literature - Tawny Lowe (17871080) (2023)
Problem Safe sleep programs have been existing since the concept was first defined in 1969. The need for health care providers to model safe sleep practices is essential for successful adherence; however, barriers to promoting safe sleep practices hinder healthcare providers' ability to implement safe sleep in hospital settings. Aim To determine the barriers to promoting safe sleep practices amongst healthcare workers in the hospital setting. Methods Whittemore & Knafl's framework (2005) guided this integrative review. CINAHL, PubMed, and Academic Search Complete databases were used as a search strategy. Inclusion criteria was limited to studies between 2010 and 2021, were peer-reviewed, in English, and quality improvement projects consisting of barriers to implementing safe sleep practices within hospitals. To assess quality of the included studies, the Mixed Methods Appraisal Tool and Standards for Quality Improvement Reporting Excellence were used. The studies were analyzed by two of the authors with data further categorized using the Social Ecological Model (SEM) to develop themes. Results Findings of the 10 included studies were presented in the form of a data display matrix. The authors used the SEM to categorize the findings under three main categories at the organizational, individual, and cultural levels. Conclusions Barriers need to be addressed in hospital settings to reduce the risk of sudden infant death syndrome. Therefore, it is vital to consider those barriers while providing teaching programs in hospital settings. Implications Findings from this review provide the core elements to consider for the development of safe sleep programs in the hospital setting. Other Information Published in: Journal of Pediatric Nursing License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.pedn.2023.03.003